2016
DOI: 10.1371/journal.pone.0161767
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective Effects of Cycloheterophyllin against UVA-Induced Damage and Oxidative Stress in Human Dermal Fibroblasts

Abstract: Ultraviolet (UV) radiation, particularly ultraviolet A (UVA), is known to play a major role in photoaging of the human skin. Many studies have demonstrated that UV exposure causes the skin cells to generate reactive oxygen species and activates the mitogen-activated protein kinase (MAPK) pathway. Previous studies have also demonstrated that cycloheterophyllin has an antioxidant effect and can effectively scavenge free radicals. Extending the aforementioned investigations, in this study, human dermal fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 52 publications
3
31
0
Order By: Relevance
“…In our study, C3G increased the low levels of p‐ERK induced by UVA. Huang et al and Hsu et al found that p‐P38 was significantly increased in HDFs after UVA irradiation, consistent with the findings of this study. Inhibition of P38 activation was sufficient to reduce hamster fibroblast cells death and apoptosis induced by moderate tunicamycin .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, C3G increased the low levels of p‐ERK induced by UVA. Huang et al and Hsu et al found that p‐P38 was significantly increased in HDFs after UVA irradiation, consistent with the findings of this study. Inhibition of P38 activation was sufficient to reduce hamster fibroblast cells death and apoptosis induced by moderate tunicamycin .…”
Section: Discussionsupporting
confidence: 92%
“…It is well known that the MAPK cascade is an important pathway in eukaryotic signal transduction networks, and it plays a key role in regulating many cytoplasmic functions and gene expression pathways. It was previously reported that UVA irradiation induces the phosphorylation of ERK, p38, and JNK . Our results showed that the p‐JNK/JNK ratio was unchanged after UVA irradiation.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In order to verify the protective effects of cycloheterophylin on fibroblasts after exposures to UVA, Huang et al . used a higher radiant exposure, 20 J cm −2 , but they started with approximately 70% cell damage. Similarly, Chan et al .…”
Section: Resultsmentioning
confidence: 99%
“…Huynh et al (19) found a 50% decrease in the viability of keratinocytes (HaCaT) with a radiant exposure of 20 J cm À2 results that corroborated those found in this study. In order to verify the protective effects of cycloheterophylin on fibroblasts after exposures to UVA, Huang et al (20) used a higher radiant exposure, 20 J cm À2 , but they started with approximately 70% cell damage. Similarly, Chan et al (10) used a radiant exposure of 20 J cm À2 in retinal epithelial cells, causing 50% cell death.…”
Section: Resultsmentioning
confidence: 99%